Description of the male of Mayriphilopterus nystalicus Mey, 2004 (Phthiraptera, Ischnocera, Philopteridae) - Valim, Michel P.; Linardi, Pedro M. (Zootaxa, 2007)
The male of Mayriphilopterus nystalicus is described and illustrated from two species of Brazilian puffbirds. The Whiteeared Puffbird (Nystalus chacuru) is confirmed as a true host for this species of chewing lice. A key for identification and a list of hosts of the six species of the genus Mayriphilopterus is provided.